2007
DOI: 10.1590/s0100-39842007000200012
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos radiológicos relevantes no diagnóstico da enterocolite necrosante e suas complicações

Abstract: A enterocolite necrosante representa uma das emergências gastrintestinais mais freqüentes e graves no período neonatal. Na suspeita clínica dessa doença, o exame radiológico simples de abdome é um procedimento de rotina, desempenhando um papel fundamental no diagnóstico, acompanhamento e detecção de complicações. No presente trabalho, realizamos uma revisão da literatura pertinente e descrevemos os achados radiológicos da enterocolite necrosante, ilustrados com casos do nosso serviço. Concluímos que o diagnóst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The radiological finding of air in the portal system, as associated with necrotizing enterocolitis, is almost always followed by intestinal pneumatosis (6,7) . In the present case, there was no evidence of pneumatosis intestinalis at radiography, but as the presence of portal air in neonates is associated with a high risk for necrotizing enterocolitis, such a diagnostic suspicion should be raised and ruled out (5)(6)(7)(8) . Subsequent radiography demonstrated that the air had disappeared and clinical and laboratory findings did not confirm the necrotizing enterocolitis hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…The radiological finding of air in the portal system, as associated with necrotizing enterocolitis, is almost always followed by intestinal pneumatosis (6,7) . In the present case, there was no evidence of pneumatosis intestinalis at radiography, but as the presence of portal air in neonates is associated with a high risk for necrotizing enterocolitis, such a diagnostic suspicion should be raised and ruled out (5)(6)(7)(8) . Subsequent radiography demonstrated that the air had disappeared and clinical and laboratory findings did not confirm the necrotizing enterocolitis hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal pneumatosis, defined as the presence of air in the intestinal wall, is characterized as a pathognomonic radiological signal of NEC. However, the most frequent radiological alteration in NEC is the generalized gastric distension of intestinal loops [17].…”
Section: Diagnosismentioning
confidence: 99%
“…Aeroportia is a finding that corresponds to fine luscism of the hepatic portal region to the peripheral region of the liver and corresponds to a practically pathognomonic finding of NEC. Other findings that may be present are the presence of portal gas, which is transitory indicating the presence of air in the portal venous system and pneumoperitoneum, with good visibility in left lateral decubitus [17,18].…”
Section: Diagnosismentioning
confidence: 99%
See 2 more Smart Citations